Alanine Transaminase levels in Patients of Dengue Fever in the Suburbs of Islamabad - Hassan Mumtaz, Irfan Afzal Mughal, Amna Faruqi, Noor -ul-Ain Irfan, Shamim Mumtaz, Asma Irfan (Journal of Rawalpindi Medical College, 2021)
Introduction: Hepatic dysfunction is a highly varied condition that can show up as minor damage with elevated levels of transaminases, or appear as extensive damage and failure of liver cells. Thus, in order to reduce associated morbidity and mortality, this ailment should be diagnosed at the earliest possible so that appropriate therapy can be instituted. Our study was carried out to observe hepatic damage in patients with dengue fever (DF) by measuring alanine transaminase levels. Materials and Methods: A cross-sectional study of three months duration was carried out in the Department of Medicine, Dr. Akbar Niazi Teaching Hospital affiliated with Islamabad Medical & Dental College, Pakistan. The sampling technique was Non-Random consecutive sampling and 118 patients were included in our study. Serum Alanine Transaminase (ALT) (normal = 7-56 IU/L), serum Aspartate Transaminase (AST) (normal = 10-40 IU/L) were determined and ultra-sound abdomen was performed. Statistical analysis was done using SPSS Version 24. The Chi-square test was used to observe the relationship between categorical variables. Phi, Cramer’s V, Pearson’s, and Spearman’s Correlation tests were used to study the association of age and gender with ALT levels. Results: There were 72% males (n=85) and 28% females (n=33). Patients were grouped according to age and mean ALT (95+86 IU/L) and AST (134.7+ 98 IU/L) levels were calculated in the different age groups. These levels were found to be significantly raised (P=0.00) in the age groups of 9-18 years and 19-25 years as compared to the other age groups. Moreover, males had high ALT levels as compared to females, however, a significant difference was not observed. There was also no association seen of gender with raised ALT levels (P=0.564), Phi & Cramer’s V=0.56, and Spearman’s correlation coefficient=0.320. Conclusions: ALT and AST levels were elevated above the normal in our sample indicating hepatic involvement.